An innocent giant - Lakhan Singh Solanki; Mandeep Dhingra; Gunjan Raghubanshi; Gurvinder Pal Thami (Wolters Kluwer Medknow Publications, 2014)
A cutaneous horn (cornu cutaneum) is a protrusion from the skin composed of a cornified material. It may be associated with a benign, premalignant, or malignant lesion at the base, masking numerous dermatoses. In a 24-year-old female, a giant cutaneous horn arising from a seborrheic keratosis located on the leg is presented. This case has been reported to emphasize that a giant cutaneous horn may also occur in young patients, even in photoprotected areas, and are not always associated with malignancy.